Virtual Tour Pariwisata Kelurahan Lahendong Berbasis Web Menggunakan Metode Prototyping - Vicky C. Mende; Quido C. Kainde; Ferdinan I. Sangkop (Pusat Riset dan Inovasi Nasional, 2023)
The virtual tour is a simulation technology that can show users a 360-degree image of a place and gives users an experience like being somewhere just by looking at a monitor screen. The tourism introduction sector in an area with beautiful destinations is very important. It needs to get good attention from the government and the community to create easy access to information. For this reason, developing the Virtual Tour website is one of the best efforts to introduce regional-owned tourism, which needs to be made to inform the wider community. The development of a website with the title